CARBONATE STABILITY AND FLUID COMPOSITION IN SUBDUCTED OCEANIC CRUST: AN EXPERIMENTAL STUDY ON H2O-CO2-BEARING BASALTS - Molina J.F.; Poli S. (My University, 2000)
Carbonates and hydrates are common products of the alteration of the upper basaltic crust in modern oceans. However, phase relationships and devolatilization reactions in altered CO2-bearing metabasalts during the subduction process are still poorly known. A series of fO2-buffered piston cylinder experiments were performed on three basaltic model compositions in the presence of a H2O–CO2 mixed fluid, at pressures from 1.0 to 2.0 GPa and temperatures from 665 to 730°C. Experimental results on a tholeiite composition demonstrate that amphibole coexists with calcite at P≤1.4 GPa, with dolomite at 1.4≤P≤1.8 GPa, and with dolomite+magnesite at pressures higher than 1.8 GPa. The stability of calcite increases with pressure with increasing Fe/(Fe+Mg) of the bulk composition. Omphacite was found in tholeiite only at 2.0 GPa, 730°C. Garnet, plagioclase, paragonite, epidote and kyanite further complicate phase relationships in the pressure range investigated. Estimates of the coexisting fluid compositions, on the basis of mass-balance and thermodynamic calculations, demonstrate the continuous H2O enrichment with increasing pressure and decreasing temperature. An almost purely aqueous fluid (<0.05) is obtained at 2.0 GPa, 665°C. Hydrous fluids and relatively high modal proportions of carbonates at high pressure and low temperature conditions are responsible for the displacement of the appearance of omphacite at higher pressures than in H2O-saturated, CO2-free systems. Modeling of devolatilization reactions along subduction zone geotherms reveals that significant decarbonation is feasible only at low pressures (in the forearc region) and at relatively high temperatures, once young oceanic crust is subducted at slow convergent rates. When the subduction process approaches steady-state conditions, CO2 is fractionated in the solid and deep recycling of CO2 is expected to account for the global-scale imbalance at convergent margins.